Analytical essay of the level of financial inclusion in Algeria (2015-2023) - Aoudia, Kahina (International journal of economic perspectives, 2025)
This article aims to measure the financial inclusion in Algeria using a multidimensional index of financial inclusion (IFI), proposed by Samra Mandira, based on the indexes of the dimensions of financial inclusion. This index will be between 0 and 1, where 0 represents a situation of complete financial exclusion, and 1 indicates a situation of complete financial inclusion. The index will be very useful for knowing the level and degree of financial inclusion in Algeria and for comparing it over time and with other countries. In order to respond to the problem of our research which is: "What is the level of financial inclusion in Algeria?", we will rely on statistical data collected from data published by the Bank of Algeria, the International Monetary Fund and the World Bank, in particular the Global Index of 2021. After analyzing the various indexes of the dimensions of financial inclusion, we were able to calculate a multidimensional index of financial inclusion for Algeria for the period from 2015 to 2023. The results indicate that this index is around 0.5 during these years, which indicates an average financial inclusion in Algeria, but which remains insufficient. Thus, it is necessary to find solutions that would allow the promotion of financial inclusion in Algeria.